PENGARUH KOMPENTENSI SUMBER DAYA MANUSIA ,PENERAPAN SISTEM AKUNTANSI DAERAH DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI PADA SKPD KABUPATEN LUMAJANG) - Maimunah, Maimunah; Made, Anwar; Setiyowati, Supami Wahyu (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2018)
This study aims to analyze the influence of human resource competencies, the application of regional accounting systems, the adoption and utilization of information technology on the quality of financial reports of local governments partially or simultaneously. in this study, the sample taken was 59 people from 9 regional work units (SKPD) consisting of financial sub-departments and accounting staff. Data collection is done through direct observation and surveys obtained by distributing questionnaires to the respondents. This research uses quantitative research methods. The results of the first research show that the competence of human resources, and the use of information technology have a positive and significant effect on the quality of the financial statements of the local government while the application of the regional accounting system does not affect the quality of the financial statements of the Lumajang regency. the competency of human resources simultaneously, the application of the regional accounting system and the use of information technology have a positive and significant effect on the quality of the financial statements of the Lumajang district government.